PERBANDINGAN PENGARUH MODEL PEMBELAJARAN ROTATING TRIO EXCHANGE DENGAN JIGSAW II TERHADAP KETERAMPILAN SOSIAL PESERTA DIDIK PADA MATA PELAJARAN IPS DI SMP NEGERI 3 PEMALI - Gita Lestari (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2018)
This research aims to test the influence of model comparison study with a Rotating Trio of Exchange with Jigsaw II towards social skills learners at IPS subjects in SMP Negeri 3 Pemali. As for the formulation of the problem: "If there are differences influence the learning model with a Rotating Trio of Exchange with Jigsaw II towards social skills learners At IPS subjects in SMP Negeri 3 Pemali?". This research is a comparative study, which uses a randomized design, completely design with the shape of the pre-post observations. The population in this research is the entire class VIII in SMP Negeri 3 Pemali. Research samples using cluster random sampling, so elected to class VIII. B as the experimental class 1 and class VIII. and as class experiment 2, each numbered 27 students. Data collection techniques are used namely observation. The hypothesis using statistics parameters i.e. two sample t-test is independent and obtained the value ≠ , hypothesis then rejected and accepted. Then there is the influence of the differences can be summed up with a Rotating Trio of Exchange model with the model Jigsaw II towards social skills learners at IPS subjects in SMP Negeri 3 Pemali. Based on the constraints in this research, it is recommended that teachers will apply the model of the Rotating Trio of Exchange and model Jigsaw II can guide learners in discussion, can control the condition in the classroom, the teacher pointed at and encourage learners to brave asking and asking opinions even though answers given lessprecise.